Loop-mediated isothermal amplification method targeting the TTS1 gene cluster for detection of Burkholderia pseudomallei and diagnosis of melioidosis. - Chantratita, N; Meumann, E; Thanwisai, A; Limmathurotsakul, D; Wuthiekanun, V; Wannapasni, S; Tumapa, S; Day, N; Peacock, S (2008)
Melioidosis is a severe infection caused by Burkholderia pseudomallei. The timely implementation of effective antimicrobial treatment requires rapid diagnosis. Loop-mediated isothermal amplification (LAMP) targeting the TTS1 gene cluster was developed for the detection of B. pseudomallei. LAMP was sensitive and specific for the laboratory detection of this organism. The lower limit of detection was 38 genomic copies per reaction, and LAMP was positive for 10 clinical B. pseudomallei isolates but negative for 5 B. thailandensis and 5 B. mallei isolates. A clinical evaluation was conducted in northeast Thailand to compare LAMP to an established real-time PCR assay targeting the same TTS1 gene cluster. A total of 846 samples were obtained from 383 patients with suspected melioidosis, 77 of whom were subsequently diagnosed with culture-confirmed melioidosis. Of these 77 patients, a positive result was obtained from one or more specimens by PCR in 26 cases (sensitivity, 34%; 95% confidence interval [CI], 23.4 to 45.4%) and by LAMP in 34 cases (sensitivity, 44%; 95% CI, 32.8 to 55.9%) (P = 0.02). All samples from 306 patients that were culture negative for B. pseudomallei were negative by PCR (specificity, 100%; 95% CI, 98.8 to 100%), but 5 of 306 patients (1.6%) were positive by LAMP (specificity, 98.4%; 95% CI, 96.2 to 99.5%) (P = 0.03). The diagnostic accuracies of PCR and LAMP were 86.7% (95% CI, 82.9 to 89.9%) and 87.5% (95% CI, 83.7 to 90.6%), respectively (P = 0.47). Both assays were very insensitive when applied to blood samples; PCR and LAMP were positive for 0 and 1 of 44 positive blood cultures, respectively. The PCR and LAMP assays evaluated here are not sufficiently sensitive to replace culture in our clinical setting.